Transformation of Lampung tapis cloth into modern fashion products through technical and material innovation: cultural and economic impacts - Hartono, Lili; Guntur, Guntur; Rustopo, Rustopo; Setiyono, Budi (International Journal of Visual and Performing Arts, 2025)
The transformation of Lampung tapis cloth into a modern fashion product through innovations in manufacturing techniques and materials used has had a significant impact on cultural and economic aspects. The purpose of this study is to analyze the transformation of tapis cloth with a focus on innovations in techniques and materials used and their impact on cultural and economic aspects. The research method used is descriptive qualitative. The data sources used are informants, places and events, and documents. This study collected data through observation, interviews, and document analysis. The data obtained were analyzed using an interactive model. The results of the study indicate that the transformation of Lampung tapis cloth through innovations in techniques and materials was carried out to adapt to the development of the times and dynamic consumer tastes, so that tapis cloth remains relevant and in demand by the wider community. The transformation of tapis cloth has an impact on the cultural aspect, namely supporting efforts to preserve regional culture, strengthening regional identity, and promoting Lampung culture to the national and international levels. In the economic aspect, the transformation of tapis cloth is able to increase people's income and absorb labor, thus providing a positive contribution to the local economy and improving people's welfare.